LEGAL POLITICAL REVIEW OF THE PROTECTION OF SEXUAL VIOLENCE VICTIMS IN THE PERSPECTIVE OF LAW NUMBER 12 OF 2022 CONCERNING SEXUAL VIOLENCE CRIMES - Ningrum, Indah Tri Kusuma (JOURNAL EQUITABLE, 2024)
Recognition of Human Rights (HR) remains a complex issue in society, particularly concerning preventive measures and protection for women in Indonesia, especially in the context of sexual violence. Despite governmental efforts to enact legislation to protect women, statistics show a dramatic increase in cases of sexual violence. One of the main obstacles is the focus on punishing perpetrators rather than prevention. To address this issue, the government ratified Law Number 12 of 2022 concerning Sexual Violence Crimes. This article discusses the process of forming this law from the perspective of legal politics, highlighting the importance of public participation and transparency in the formation of legislation that is responsive to the protection of victims of sexual violence. Law Number 12 of 2022 concerning Sexual Violence Crimes demonstrates the government's efforts to consider the public interest and involve the community in the legislative process, as well as provide transparency in the provision of related information.